Defining Dignity and Its Place in Human Rights. Issue 1 (1st January 2014) - Michael, Lucy
Abstract: The concept of dignity is widely used in society, particularly in reference to human rights law and bioethics. Several conceptions of dignity are identified, falling broadly within two categories: full inherent dignity (FID) and non-inherent dignity (NID). FID is a quality belonging equally to every being with full moral status, including all members of the human natural kind; it is permanent, unconditional, indivisible and inviolable. Those beings with FID ought to be treated deferentially by others by virtue of their belonging to a noble caste. FID grounds fundamental human rights, such as the rights to freedom and equality. The concept of dignity forms a network of interconnected ideas related to worth and value particularly within legal and ethical discourse; it is a rich and meaningful concept, irreducible to one or two quasi-legal principles. Fundamentally, dignity matters because it forms the foundation of civilized society; without it, serious abuse of people is more likely to occur.